2020
DOI: 10.1055/s-0040-1707239
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Iridium-Catalyzed Hydrosilylation of Alkenes and Alkynes

Abstract: Hydrosilylation of multiple carbon–carbon bonds is a well-known process for the construction of organosilicon compounds. Nowadays, precious metal catalysts, especially platinum complexes, still occupy dominant positions in such processes. However, one important member of the precious metal family, iridium, is less used in this field. As early research mainly focused on developing stable and effective iridium catalysts, recent advances have disclosed the specific efficiency of simple iridium catalytic systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Concerning Ir( iii )-catalysed hydrosilylation reactions, a range of different reducible functional groups have been evaluated, including alkenes, alkynes, amides, C=heteroatom compounds. 65–68 It is noticeable that as part of many of these studies, mechanisms have been proposed where iridacycles feature as one of the catalytically active species, which is supported by both computational as well as experimental evidence. 62,65,66,69 These studies highlighted the importance of Ir( iii ) metallacycles and how their associated catalytic activity may be improved through ligand development.…”
Section: Resultsmentioning
confidence: 80%
“…Concerning Ir( iii )-catalysed hydrosilylation reactions, a range of different reducible functional groups have been evaluated, including alkenes, alkynes, amides, C=heteroatom compounds. 65–68 It is noticeable that as part of many of these studies, mechanisms have been proposed where iridacycles feature as one of the catalytically active species, which is supported by both computational as well as experimental evidence. 62,65,66,69 These studies highlighted the importance of Ir( iii ) metallacycles and how their associated catalytic activity may be improved through ligand development.…”
Section: Resultsmentioning
confidence: 80%
“…Organosilicon compounds have recently received remarkable attention both in academic and in industrial fields for their various attractive physical properties, ease of manipulation and widely applications in materials science, aerospace, electronics and electrical, architecture, environment, energy resources, and biomedical because they usually contain stable and inert C–Si bonds in comparison with ordinary organocarbon compounds. Thus, various silicone products such as silicone rubber, silicone oil, silicone coupling agents, and silicone resin have been developed for their high-temperature resistance, low-temperature resistance, good hydrophobicity, high transparency, lubricity, anti-stickiness, and victory inertia and are widely used in modern industry, organic synthesis, and the above mentioned usages and other fields. It is also reported the synthesized silicone compounds and their derivatives could be utilized as light-emitting diodes for organic electron transport materials . It is also demonstrated that replacement of carbon with silicon in a compound can change its physical and chemical properties, which in turn changes its biological activity to make it have better life and pharmaceutical chemistry value, so the introduction of silicon provides more space for drug design for its inherent nontoxicity …”
Section: Introductionmentioning
confidence: 99%
“…Although organosilicon compounds have been visualized notable applications, no natural organic silicon compounds have been found so far. Therefore, the development of efficient applicable methods for the synthesis of organic silicon compounds has become the focus point. ,, Compared with other methods, metal-catalyzed hydrosilylation of unsaturated organic substrates such as olefins and alkynes to construct various Si–X (X = C, N, O, etc.) bonds is a particularly powerful and effective method to obtain organosilicon compounds with high atomic economy under mild reaction conditions, represents the most efficient and direct protocol for the synthesis of various silicon-based functionalized organic molecules, and plays an important role in organic and materials chemistry. The hydrosilylation of olefins with rare-earth metal as catalysts was first reported by Marks and co-workers utilizing Cp′ 2 LnCH­(SiMe 3 ) 2 , Me 2 SiCp″ 2 LnCH­(SiMe 3 ) 2 , and Me 2 SiCp″(R*C 5 H 4 )­LnCH­(SiMe 3 ) 2 (Cp′ = η 5 -Me 5 C 5 ; Cp″ = η 5 -Me 4 C 5 ; Ln = lanthanide; R* = chiral auxiliary) as catalysts that do not require a cocatalyst .…”
Section: Introductionmentioning
confidence: 99%
“…3 During the past decades, catalytic hydrosilylation of unsaturated C–C bonds has been established as one of the most straightforward methods and atom-economical approaches for the preparation of value-added organosilanes. 4 In this context, tremendous efforts have been made toward the Markovnikov or anti-Markovnikov hydrosilylation reactions of alkenes 5 and alkynes. 6 These reactions currently are not only utilized on the laboratory scale, but also have been widely implemented in the chemical industry.…”
mentioning
confidence: 99%